Chitosan-dextran sulfate hydrogels as a potential carrier for probiotics - Falco, Cigdem Yucel (2019)
Physical and chemical (crosslinked with genipin) hydrogels based on chitosan and dextran sulfate were developed and characterized as novel bio-materials suitable for probiotic encapsulation. The swelling of the hydrogels was dependent on the composition and weakly influenced by the pH of the media. The morphology analysis supports the swelling data showing distinct changes in microstructure depending on the composition. The viability and culturability tests showed approx. 3.6 log CFLI/mL decrease of cells (L acidophilus as model) incorporated into chemical hydrogels when compared to the number of viable native cells. However, the live/dead viability assay evidenced that a considerable amount of viable cells were still entrapped in the hydrogel network and therefore the viability is most likely underestimated. Overall, the developed systems are robust and their structure, rheology and swelling properties can be tuned by changing the blend ratio, thus constituting appealing bio-matrices for cell encapsulation. (C) 2017 Elsevier Ltd. All rights reserved.